2022
DOI: 10.3389/fpsyg.2022.928533
|View full text |Cite
|
Sign up to set email alerts
|

Can People Intentionally and Selectively Forget Prose Material?

Abstract: List-method directed forgetting (LMDF) is the demonstration that people can intentionally forget previously studied information when they are asked to forget what they have previously learned and remember new information instead. In addition, recent research demonstrated that people can selectively forget when cued to forget only a subset of the previously studied information. Both forms of forgetting are typically observed in recall tests, in which the to-be-forgotten and to-be-remembered information is teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…The inconsistent results in SDF effects caused by different materials were also found between our study and the study of Pastötter and Haciahmet (2022). In their study, meaningful prose materials were adopted and no SDF effects were observed.…”
Section: Methodscontrasting
confidence: 63%
See 4 more Smart Citations
“…The inconsistent results in SDF effects caused by different materials were also found between our study and the study of Pastötter and Haciahmet (2022). In their study, meaningful prose materials were adopted and no SDF effects were observed.…”
Section: Methodscontrasting
confidence: 63%
“…In their study, meaningful prose materials were adopted and no SDF effects were observed. Pastötter and Haciahmet (2022) suggested that the prose might be relatively complex and not influenced by the forgetting cues. In addition, a lower recall rate for List 2 was found in the forgetting condition than in the imagining condition, and there were no recall differences for List 1 between these two conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations